PKM PEMBUATAN KEMASAN DAN PERLUASAN PEMASARAN MINUMAN SARI BUAH NANAS KHAS KABUPATEN SUBANG JAWA BARAT - Opan Arifudin (Aptekmas Jurnal Pengabdian pada Masyarakat, 2020)
Pineapple is a typical fruit of Subang Regency, but not all pineapples can be sold in the market. This is due to the size of the pineapple that is not all the same, even more small sizes that can not be sold on the market. So as to take advantage of the small size of pineapple, pineapple juice is processed. Therefore, pineapple juice is one of the products of SMEs in Subang Regency. But the problem faced by businesses or small industries today is industrial management and marketing. With community service related to UMKM assistance on the type of pineapple juice traditional drink is expected to provide solutions in improving the welfare of MSMEs. The problem solving method used is based on a management approach in increasing production and sales results with 4 (four) stages of program implementation, namely preparation and planning, implementation of activities, monitoring and evaluation and reflection. The community service program carried out is with packaging innovation in accordance with the rules of the Subang City Health Office and marketing expansion on online platforms and social media.